TOEFL Score of Tadris Chemistry Students at UIN Antasari in Achievement of CEFR Standard - Oktapianti, Siska (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2024)
This paper aims to explain the TOEFL score achieved by Tadris Chemistry students at UIN (State Islamic University) Antasari Banjarmasin towards achieving the CEFR (Common European Framework Reference) standard. The sample is 20 Tadris Chemistry Students for the Teaching of Chemistry Class, Odd Semester 2022/2023. The method used is descriptive method. The results show that of the 20 students taking the TOEFL, in listening session , there are 6 people (30%) below the CEFR level and 14 people (70%) getting the A2 level. The results of the score obtained in structure and written expression from 20 students get the A2 level. The score results in this reading comprehension session, all participants get A2 level so that 100% of students get A2 level. For the total TOEFL scores obtained from 20 students, the result obtained is in the range of 310-443 (A2 level according to the CEFR level standard).